Anyflip-Assisted E-Book to Enhancing Elementary School Students' Motivation - Permata, Azrina; Zulherman (International Journal of Elementary Education, 2023)
Appropriate learning media must be developed to boost students' learning motivation and conceptual comprehension. E-books are required as a form of instructional media to present subject-related content with student-workable evaluation questions. The primary objective of the research and development of this Anyflip-assisted e-book is to enhance student motivation. The study employs the ADDIE model, which comprises five stages: Analysis, Design, Development, Implementation, and Evaluation. The research data was collected through observation methods and administering a questionnaire, followed by a pre-test and a post-test. The study participants comprised 64 elementary school students in the fifth grade in two elementary School. The present investigation employs N-Gain Score analysis to assess the efficacy of anyflip-assisted e-books in enhancing student motivation. Additionally, the study aims to determine distinctions between the experimental and control classes by utilizing the T-test and the One Group Pre-test and Post-test Design. The study's findings indicate that the e-book development process is highly efficacious. This Anyflip-assisted e-book learning medium is feasible and can potentially enhance student motivation, particularly among fifth-grade elementary school students.